Macroeconomic Analysis On Indonesia Green Sukuk: Co-Integration And Vector Error Correction Mechanism (Vecm) Model Approach - Jaiz, Muhammad (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2024)
The performance of Indonesia Islamic green bonds or green Sukuk can be influenced by many factors such as internal and external. External variables will be used in this study, namely macroeconomic influenced. This study aims tried to analyze the long and short-term influence of macroeconomic variables such as inflation, BI rate (benchmark interest rate), exchange rate, and stock price exchange on the performance of Indonesia green bonds and green Sukuk for the periods from 2018 to 2020. This quantitative study applied the method of the co-integration approach of Vector Error Correction Mechanism (VECM) to examine the short-term and long-term impacts among macroeconomic variables through EVIEWS software. The authors carried out a long-term correlation analysis on these variables using the co-integration test. The Vector Error Correction Model (VECM) was used in the analysis because the results of the stationary test obtained stationary data at first difference and have long-term co-integration. The results showed that the macroeconomics variables are based on the empirical findings that the inflation rate, exchange rate, and stock exchange have a co-integration in the short-term and long run with the green Sukuk performance. It is different from the Bank Indonesia rate variables of co-integration in the long-term period to green Sukuk performance. The investors should pay attention to the exchange rate and stock exchange movements because both variables have short and long-term effects on green Sukuk. Hence, the investors also need to pay attention to changes in the inflation because it influences green Sukuk return in the long run.